2013
DOI: 10.1016/j.ydbio.2013.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of Dishevelled in convergently extending mesoderm

Abstract: Convergent extension (CE) is a conserved morphogenetic movement that drives axial lengthening of the primary body axis and depends on the planar cell polarity (PCP) pathway. In Drosophila epithelia, a polarised subcellular accumulation of PCP core components, such as Dishevelled (Dvl) protein, is associated with PCP function. Dvl has long been thought to accumulate in the mediolateral protrusions in Xenopus chordamesoderm cells undergoing CE. Here we present a quantitative analysis of Dvl intracellular localis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Co-injection of the two constructs interfered with expression of both, a phenomenon we have observed with other proteins 45 . However, injection of GFP-PI4K2β wild type and mCherry-PI4K2β SA mutant into nearby parts of same embryo highlighted that GFP-PI4K2β wild type is more basolaterally localised than the mCherry-PI4K2β SA mutant ( Fig.5F-F").…”
Section: Phosphorylation Of Serine-265 By Par-1 Regulates the Subcellsupporting
confidence: 53%
“…Co-injection of the two constructs interfered with expression of both, a phenomenon we have observed with other proteins 45 . However, injection of GFP-PI4K2β wild type and mCherry-PI4K2β SA mutant into nearby parts of same embryo highlighted that GFP-PI4K2β wild type is more basolaterally localised than the mCherry-PI4K2β SA mutant ( Fig.5F-F").…”
Section: Phosphorylation Of Serine-265 By Par-1 Regulates the Subcellsupporting
confidence: 53%
“…Similar to the asymmetric distribution of the core PCP components in Drosophila epithelia, asymmetric localization of core PCP proteins expressed as fluorescent fusion proteins was observed in mediolaterally polarized cells during zebrafish gastrulation, with Pk-GFP and Dvl-GFP fusion proteins being enriched at the anterior and posterior cell membranes, respectively (Ciruna et al, 2006;Yin et al, 2008). By contrast, in Xenopus Dvl is enriched at the cell edges facing the notochord-somite boundary (Panousopoulou et al, 2013). Yet, C&E movements in Xenopus explants are controlled by PCP core proteins via the Septin cytoskeleton and its ability to regulate cortical actomyosin compartmentalization and the remodeling of cell-cell contacts (Shindo and Wallingford, 2014).…”
Section: Introductionmentioning
confidence: 71%
“…Live imaging of mesodermal cells in Xenopus, zebrafish and mouse embryos shows that perturbation of PCP signaling disrupts mediolateral polarity and stability of mesodermal cell protrusions, their mediolateral alignment and elongation, and the polarization of both the medial and radial intercalations that normally serve to narrow and extend the AP axis (Table 1) (Darken et al, 2002;Heisenberg et al, 2000;Jessen et al, 2002;Takeuchi et al, 2003;Veeman et al, 2003;Wallingford et al, 2000;Yen et al, 2009;Yin et al, 2008). Although Dvl was initially reported to localize to mediolateral protrusions, where it was thought to promote actin polymerization (Kinoshita et al, 2003), this was subsequently found to be illusory (Panousopoulou et al, 2013). Instead, work in zebrafish has identified a more classically planar polarized distribution of PCP proteins in mediolaterally elongated mesodermal cells during CE (Fig.…”
mentioning
confidence: 99%